Perancangan Sistem Informasi Kelurahan Berbasis Website Dengan Metode Object Oriented Analysis And Design (Ooad), (Studi Kasus Kelurahan Masmambang, Kabupaten Seluma) - A.R Walad Mahfuzhi; Agung Kharismaah Hidayah; Muhammad Husni Rifqo; Andrean Suryadinata Justicia (UNIVED Press, 2025)
The rapid advancement of information technology has encouraged government institutions, including urban villages, to innovate in improving the quality of public services through the implementation of digital information systems. Masmambang Urban Village, located in Seluma Regency, still faces several challenges, particularly in terms of information dissemination and administrative management, which are still carried out manually. This results in inefficient and less transparent service processes. To address these issues, this study aims to design a web-based information system capable of integrating administrative functions and information dissemination in an optimal manner. The study employs the Object-Oriented Analysis and Design (OOAD) method, applying an object-oriented approach to build a system structure that is organized, flexible, and easy to develop. The design process includes system requirements analysis, modeling using UML diagrams (Use Case, Class, and Sequence Diagrams), and database design using MySQL. The system features include letter service management, news publication, activity photo galleries, village profiles, contact forms, and service request status tracking. Based on the design results, the system can improve operational efficiency and information accessibility, while also enhancing transparency in administrative services in a digital and real-time manner. Therefore, this system is expected to be a suitable solution to support the digitalization process within the village government environment.